math

posted by .

Prove the identity:
1-cos2x/sin2x = 1+tanx/1+cotx

I simplified the RS to tanx.
LS:(1-2cos²x+1)/2sinxcosx
(2+2cos²x)/2sinxcosx

How do I simplify the rest?

  • math -

    change the LS to
    (1 - (1 - 2sin²x))/(2sinxcosx)
    = 2sin²x/(2sinxcox)
    = sinx/cosx
    = tanx = RS

  • math -

    thanks! I've been trying to get this one for quite awhile. So many options to choose :(

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math

    1)A piano tuner uses a tuning fork. If middle C has a frequency of 264 vibrations per second, write an equation in the form d=sinw(t) for the simple harmonic motion. 2) Verify the identity tan^2X-cot^2X/tanX+cotX=tanX-cotX I'm not …
  2. Math - Trig - Double Angles

    Prove: sin2x / 1 - cos2x = cotx My Attempt: LS: = 2sinxcosx / - 1 - (1 - 2sin^2x) = 2sinxcosx / - 1 + 2sin^2x = cosx / sinx - 1 = cosx / sinx - 1/1 = cosx / sinx - sinx / sinx -- Prove: 2sin(x+y)sin(x-y) = cos2y - cos2x My Attempt: …
  3. Math, derivatives

    f(x) = x² + 2Cos²x, find f ' (x) a) 2(x+cos x) b) x - sin x c) 2x + sin x d)2(x - sin2x) I got neither of these answers, since the 2nd part should be chain rule, right?
  4. Trig check my work please?

    tan(X+30)tan(30-x)=2cos2x-1 / (2cos2x+1) i just did (tanx)(-tanx)=-sin^2x/cos^2x would that work?
  5. Calculus

    Solve identity, (1-sin2x)/cos2x = cos2x/(1+sin2x) I tried starting from the right side, RS: =(cos²x-sin²x)/(1+2sinxcosx) =(cos²x-(1-cos²x))/(1+2sinxcosx) and the right side just goes in circle. May I get a hint to start off?
  6. Math

    simplify (cos4x-cos2x)/(sin4x+sin2x) the answer choices are : cotx, tanx, cotxtanx, or 1
  7. Math please help quick

    Which of the following are identities? Check all that apply. (Points : 2) sin2x = 1 - cos2x sin2x - cos2x = 1 tan2x = 1 + sec2x cot2x = csc2x - 1 Question 4. 4. Which of the following equations are identities?
  8. Precalculus/Trig

    Prove the following identity: 1/tanx + tanx = 1/sinxcosx I can't seem to prove it. This is my work, I must've made a mistake somewhere: Converted 1/tanx: 1/sinx/cosx + sinx/cosx = 1/sinxcosx Simplified 1/sinx/cosx: cosx/sinx + sinx/cosx …
  9. Trigonometry

    Prove: 1-tanx/1+tanx=1-sin2x/cos2x
  10. a math

    Prove cotx-1/cotx+1 = sec2x - tan2x I prove till cotx-1/cotx+1 =1/1+tanx - tanx/1+tanx

More Similar Questions